2023
DOI: 10.1002/pc.27346
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of nanoparticle and stretch‐induced orientation on crystal structure and properties of UHMWPE/TiO2 composite microporous membranes

Abstract: The nanocomposite microporous membrane of ultra-high molecular weight polyethylene (UHMWPE) and nano-titanium dioxide (nano-TiO 2 ) system was prepared by combining the thermally induced phase separation (TIPS) technique with the extrusion-casting process using liquid paraffin (LP) as the diluent. The effects of variations of TiO 2 content and melt draw ratio on the properties of composite microporous membranes were studied and the optimal processing parameters were further investigated. ATR-FTIR demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In recent years, scientists have focused primarily on functionalizing PE membranes through surface modification to enhance properties including wettability, strength, and thermal and dimensional stability, encompassing both inorganic and organic coatings [ 23 , 81 , 178 , 179 ]. Specifically, inorganic reinforcement materials, such as SiO 2 , Al 2 O 3 , TiO 2 , ZrO 2 and so on, can be incorporated into the PE matrix to prevent membrane deformation under elevated temperature conditions and further enhance the safety of LIBs, due to their excellent heat resistance and function as a physical skeleton [ 81 , 173 , 180 ].…”
Section: Recent Progress In Polymer-based Porous Separator Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, scientists have focused primarily on functionalizing PE membranes through surface modification to enhance properties including wettability, strength, and thermal and dimensional stability, encompassing both inorganic and organic coatings [ 23 , 81 , 178 , 179 ]. Specifically, inorganic reinforcement materials, such as SiO 2 , Al 2 O 3 , TiO 2 , ZrO 2 and so on, can be incorporated into the PE matrix to prevent membrane deformation under elevated temperature conditions and further enhance the safety of LIBs, due to their excellent heat resistance and function as a physical skeleton [ 81 , 173 , 180 ].…”
Section: Recent Progress In Polymer-based Porous Separator Membranesmentioning
confidence: 99%
“…Notably, UHMWPE has occupied a substantial market share in commercial LIB separators, owing to its superior microporous structure, puncture resistance, mechanical strength, chemical resistance, cost-effectiveness, thermal stability, and so on [ 173 , 174 , 175 , 176 , 177 ]. Just like conventional PE-based components, the performance of a UHMWPE membrane can also be enhanced when used as a battery separator through the introduction of inorganic materials (e.g., SiO 2 , Al 2 O 3 , TiO 2 , and ZrO 2 ) and organic materials (e.g., PVDF, PMMA) to enhance thermal stability and improve the safety of LIBs [ 173 , 180 ]. As an illustration, Babiker et al [ 99 ] efficiently engineered and industrialized UHMWPE/SiO 2 nanocomposite membranes for the first time by means of a biaxial stretching without additional post-modifications.…”
Section: Recent Progress In Polymer-based Porous Separator Membranesmentioning
confidence: 99%
“…5,6 Among the pool of polymers, ultrahigh molecular weight polyethylene (UHMWPE) is extensively explored for biomedical [7][8][9] and ballistic applications. [10][11][12][13][14][15][16] Owing to high tensile strength and flexibility, UHMWPE has a low melting temperature (<155 C) and is viscoelastic, thus can only be utilized in a low-temperature window. 17,18 VO 2 -based UHMWPE polymer composite was recently explored for its high-temperature mechanical strength by the split Hopkinson pressure bar test by Verma et al 19 It was shown that above 75 C, the VO 2 -based UHMWPE exhibits increased dynamic mechanical strength, because of the phase transition of VO 2 from monoclinic to tetragonal, consequently leads to an increase in elastic modulus and hardness.…”
Section: Introductionmentioning
confidence: 99%